A review on the auxetic mechanical metamaterials and their applications in the field of applied engineering - Siniauskaya, Volha; Wang, Hao; Liu, Yadong; Chen, Yuhang; Zhuravkov, Michael; Lyu, Yongtao (Frontiers in Materials, 2024)
Metamaterials are artificially created materials or structures with properties not found in nature. They encompass electromagnetic, acoustic, and mechanical metamaterials, which are particularly significant in applied engineering. Mechanical metamaterials exhibit unique mechanical properties such as vanishing shear modulus, negative Poisson’s ratio, negative compressibility, etc. This paper reviews the most commonly used mechanical metamaterials and discusses their applications in the field of applied engineering, specifically in vibration isolation, energy absorption, and vibration reduction. The prospects for future developments in this field are also presented.